Valery K. Ivchenko - «SISJ NAMS Ukraine», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article is dedicated to the memory of doctor of medical Sciences Professor V. K. Ivchenko - talented organizer of healthcare.